Rosmarinic Acid Activates AMPK to Inhibit Metastasis of Colorectal Cancer - Han, Yo-Han; Kee, Ji-Ye; Hong, Seung-Heon (Frontiers in Pharmacology, 2018)
Rosmarinic acid (RA) has been used as an anti-inflammatory, anti-diabetic, and anti-cancer agent. Although RA has also been shown to exert an anti-metastatic effect, the mechanism of this effect has not been reported to be associated with AMP-activated protein kinase (AMPK). The aim of this study was to elucidate whether RA could inhibit the metastatic properties of colorectal cancer (CRC) cells via the phosphorylation of AMPK. RA inhibited the proliferation of CRC cells through the induction of cell cycle arrest and apoptosis. In several metastatic phenotypes of CRC cells, RA regulated epithelial–mesenchymal transition (EMT) through the upregulation of an epithelial marker, E-cadherin, and the downregulation of the mesenchymal markers, N-cadherin, snail, twist, vimentin, and slug. Invasion and migration of CRC cells were inhibited and expressions of matrix metalloproteinase (MMP)-2 and MMP-9 were decreased by RA treatment. Adhesion and adhesion molecules such as ICAM-1 and integrin β1 expressions were also reduced by RA treatment. In particular, the effects of RA on EMT and MMPs expressions were due to the activation of AMPK. Moreover, RA inhibited lung metastasis of CRC cells by activating AMPK in mouse model. Collectively, these results proved that RA could be potential therapeutic agent against metastasis of CRC.